2021
DOI: 10.1111/are.15497
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of mud crab, genusScyllabetween sexes based on morphological and physiological characteristics

Abstract: Genus Scylla has been well documented by Keenan (1997), which divided the mud crab into four species, namely S. serrata, S. paramamosain, S. olivacea and S. tranquebarica. The taxonomy of the genus Scylla had been critically revised through morphometric measurements and further confirmed through powerful tools such as alloenzyme electrophoresis and mitochondrial DNA sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…Each treatment group consisted of 30 individuals of mud crabs, including the control group. Only crabs with Stage 4 of ovarian maturation were taken into the study as the ovary at this stage undergoes ripening, thus indicating its readiness to spawn [11]. As the ovaries are not externally visible due to the hard and thick carapace, hence, we have inspected the maturity of mud crab ovary by carefully depressing and pushing forward 2…”
Section: Feeding Trial and Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each treatment group consisted of 30 individuals of mud crabs, including the control group. Only crabs with Stage 4 of ovarian maturation were taken into the study as the ovary at this stage undergoes ripening, thus indicating its readiness to spawn [11]. As the ovaries are not externally visible due to the hard and thick carapace, hence, we have inspected the maturity of mud crab ovary by carefully depressing and pushing forward 2…”
Section: Feeding Trial and Experimental Conditionsmentioning
confidence: 99%
“…The presence of hormones, particularly the vertebrate-type steroids such as progesterone (Pg) and estradiol (E 2 ) hormones, have been reported in the hepatopancreas, ovary, and hemolymph of Chinese white shrimp Penaeus chinensis [7], green mud crab Scylla serrata [8], blue pearl crayfish Cherax albidus [9], narrow-clawed crayfish Astacus leptodactylus [10], and swimming crab Portunus trituberculatus [6]. In general, E 2 and Pg play a vital role in crustacean reproduction via enhancing the initiation of related metabolic pathways during vitellogenesis [11,12], but their concentrations with ovarian maturation stages vary between species. Interestingly, the changes in the vertebrate type of steroids titer during oocyte maturation indicate their importance in governing the vitellogenesis process, which involves the mobilization of lipids from the storage sites [13].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of each fattening period, the crabs were subjected to dissection of hepatopancreas and ovaries for growth performance, and morphological and biochemical analyses. Only crabs with Stage 4 of ovarian maturation were taken into the study as the ovary at this stage is ripen, which indicated its readiness to spawn (Hidir et al, 2021). The subsequent analyses of the captive crabs after fattening periods were compared with the wild-caught carbs (control) from Stage 4 as reference.…”
Section: Feeding Experimentsmentioning
confidence: 99%
“…This study was conducted to determine if T. anomala shows dimorphism in morphological characters. Sexual dimorphism in size and morphological characters is common in many crustaceans (Alencar et al, 2014;Hidir et al, 2021). We hypothesized that the weight, carapace width, carapace length, total length and 4 th abdominal segment of males and females of T. anomala are different.…”
Section: Ecological Characteristicsmentioning
confidence: 99%